Analisis Tindak Tutur Direktif Dalam Film Ayat-ayat Adinda Sutradara Hestu Saputra Dalam Rangka Pembelajaran Berbicara Di Kelas XI SMA - Sukma Berlianti Fiqri; Bagiya Bagiya; Umi Faizah (Pendidikan Bahasa dan Sastra Indonesia, 2022)
Abstract: This research aims to describe: (1) the form of directive speech acts; and (2) learning speaking skills using the film Ayat-ayat Adinda, director Hestu Saputra, for XI high school students. This research is a qualitative descriptive study. Research data is in the form of speech in the film Ayat-ayat Adinda directed by Hestu Saputra. Data collection was carried out using free listening and speaking techniques and note-taking techniques. Data analysis used the matching method with content analysis techniques. The results of data analysis are presented with informal techniques. Based on the data and discussion, it is concluded that: (1) The form of directive speech acts in the film Ayat-ayat Adinda director Hestu Saputra there are six types of directive speech acts, namely: request found 4 data, command found 2 data, prohibition found 5 data, granting permission was not found data, advice found 5 data and questions found 5 data; (2) learning speaking skills using film media Adinda's verses directed by Hestu Saputra to class XI SMA students are made based on KD 3.19 Analyzing the content and language of drama/films that are read or watched, using the cooperative learning method with the STAD (Student Team Achievement Division) scientifically based, and learning evaluation consists of three aspects, namely: effective assessment, cognitive assessment, and psychomotor assessment. Keywords: directive speech act, lesson plan implementation.